Transcriptome analysis reveals molecular mechanisms of lymphocystis formation caused by lymphocystis disease virus infection in flounder (Paralichthys olivaceus) - Zhang, Honghua; Sheng, Xiuzhen; Tang, Xiaoqian; Xing, Jing; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2023)
Lymphocystis disease is frequently prevalent and transmissible in various teleost species worldwide due to lymphocystis disease virus (LCDV) infection, causing unsightly growths of benign lymphocystis nodules in fish and resulting in huge economic losses to aquaculture industry. However, the molecular mechanism of lymphocystis formation is unclear. In this study, LCDV was firstly detected in naturally infected flounder (Paralichthys olivaceus) by PCR, histopathological, and immunological techniques. To further understand lymphocystis formation, transcriptome sequencing of skin nodule tissue was performed by using healthy flounder skin as a control. In total, RNA-seq produced 99.36%-99.71% clean reads of raw reads, of which 91.11%-92.89% reads were successfully matched to the flounder genome. The transcriptome data showed good reproducibility between samples, with 3781 up-regulated and 2280 down-regulated differentially expressed genes. GSEA analysis revealed activation of Wnt signaling pathway, Hedgehog signaling pathway, Cell cycle, and Basal cell carcinoma associated with nodule formation. These pathways were analyzed to interact with multiple viral infection and tumor formation pathways. Heat map and protein interaction analysis revealed that these pathways regulated the expression of cell cycle-related genes such as ccnd1 and ccnd2 through key genes including ctnnb1, lef1, tcf3, gli2, and gli3 to promote cell proliferation. Additionally, cGMP-PKG signaling pathway, Calcium signaling pathway, ECM-receptor interaction, and Cytokine-cytokine receptor interaction associated with nodule formation were significantly down-regulated. Among these pathways, tnfsf12, tnfrsf1a, and tnfrsf19, associated with pro-apoptosis, and vdac2, which promotes viral replication by inhibiting apoptosis, were significantly up-regulated. Visual analysis revealed significant down-regulation of cytc, which expresses the pro-apoptotic protein cytochrome C, as well as phb and phb2, which have anti-tumor activity, however, casp3 was significantly up-regulated. Moreover, bcl9, bcl11a, and bcl-xl, which promote cell proliferation and inhibit apoptosis, were significantly upregulated, as were fgfr1, fgfr2, and fgfr3, which are related to tumor formation. Furthermore, RNA-seq data were validated by qRT-PCR, and LCDV copy numbers and expression patterns of focused genes in various tissues were also investigated. These results clarified the pathways and differentially expressed genes associated with lymphocystis nodule development caused by LCDV infection in flounder for the first time, providing a new breakthrough in molecular mechanisms of lymphocystis formation in fish.